Jasmonate induced alternative splicing responses in Arabidopsis. (26th August 2020) - Feng, Guanqiao; Yoo, Mi‐Jeong; Davenport, Ruth; Boatwright, J. Lucas; Koh, Jin; Chen, Sixue; Barbazuk, W. Brad
Abstract: Jasmonate is an essential phytohormone regulating plant growth, development, and defense. Alternative splicing (AS) in jasmonate ZIM‐domain (JAZ) repressors is well‐characterized and plays an important role in jasmonate signaling regulation. However, it is unknown whether other genes in the jasmonate signaling pathway are regulated by AS. We explore the potential for AS regulation in three Arabidopsis genotypes (WT, jaz2, jaz7 ) in response to methyl jasmonate (MeJA) treatment with respect to: (a) differential AS, (b) differential miRNA targeted AS, and (c) AS isoforms with novel functions. AS events identified from transcriptomic data were validated with proteomic data. Protein interaction networks identified two genes, SKIP and ALY4 whose products have both DNA‐ and RNA‐binding affinities, as potential key regulators mediating jasmonate signaling and AS regulation. We observed cases where AS alone, or AS and transcriptional regulation together, can influence gene expression in response to MeJA. Twenty‐one genes contain predicted miRNA target sites subjected to AS, which implies that AS is coupled to miRNA regulation. We identified 30 cases where alternatively spliced isoforms may have novel functions. For example, AS of bHLH160 generates an isoform without a basic domain, which may convert it from an activator to a repressor. Our study identified potential key regulators in AS regulation of jasmonate signaling pathway. These findings highlight the importance of AS regulation in the jasmonate signaling pathway, both alone and in collaboration with other regulators. Significance statement: By exploring alternative splicing, we demonstrate its regulation in the jasmonate signaling pathway alone or in collaboration with other posttranscriptional regulations such as nonsense and microRNA‐mediated decay. A signal transduction network model for alternative splicing in jasmonate signaling pathway was generated, contributing to our understanding for this important, prevalent, but relatively unexplored regulatory mechanism in plants.